Shah Waliullah's contributions towards Islamic revivalism in India - Qasemy, Mohammad Abdul Qaiyum (Kulliyyah of Islamic Revealed knowledge and Human Sciences,International Islamic University Malaysia, 1998)
Shah Waliullah pioneered an Islamic revivalist movement and helped to reconstruct the religious and political thought in Islam. He formed a bridge between medieval and modern Islam in India. The purpose of this study is to describe, analyse and evaluate Shah Waliullah's contributions to Islamic reawakening in India. This study has mostly relied on libra..ry research. Shah Waliullah lived at a time of social and political turmoil. During that dismal and difficult moment Shah Waliullah's emergence was a ray of hope for the Ummah. He observed the moral degeneration of the Ummah and their deviation from the right path. He criticised all their deviations and contributed to revive the real spirit of Islam in the minds of the Muslims. This study found that he propounded Islam as a complete code of life and he firmly believed that without the implementation of Shari'ah, Islamic life can not be enjoyed. He wanted to see a peaceful society in the light of the Qur 'an and Sunnah. Moreover it is also seen that he presented comprehensive ideas of the Khilafah and pointed out all the elements necessary for a stable state. Thus, it was very essential for him to lead a strong movement to implement his ideas. However, Shah Waliullah's political reformation and movement could not reach the pinnacle of its aim.